Synovial Chondromatosis of the Hip Joint: A Case Report - Shrestha, Sailendra Kumar Duwal; Shrestha, Mahendra Raj; Nepal, Prabin; Maharjan, Rajendra; Lamichhane, Suman; Shrestha, Kumar (Annapurna Journal of Health Sciences, 2023)
Synovial chondromatosis of the hip joint is a rare, benign synovial disorder that results in loose body formation because of metaplastic transformation. The diagnosis of hip involvement is frequently delayed due to the gradual onset of symptoms. In this case, the radiographic features were not conclusive, so we performed an ultrasound-guided synovial biopsy before surgical intervention. Arthroscopic-assisted mini-open surgery was used to treat the synovial chondromatosis of the hip joint. There were no issues during the procedure or afterward. The patient was symptom-free and had no radiological signs of a recurrence at the most recent check-up. The recurrence rate could be decreased by using the arthroscopic-assisted mini-open technique to complete the objectives of thorough synovectomy, debridement, and loose body removal. This technique lowers the risk of surgical complications by preventing femoral head dislocation. We present synovial chondromatosis of the hip in our study, and to our knowledge, no paper has been published in our setting till date.